Microcredit as a proposal for a new paradigm - Mendoza de la Cruz, Heriberto (Universidad Francisco de Paula Santander, 2015)
The microcredit policy for poor people, impacting the three dimensions: Economic Welfare, Social Rights and Territorial Context, to this day has had no impact on the quality of life of the beneficiaries in the essential and basic aspects, such as decent food. The micro-financing scheme must take a new course, which will allow us to avoid the systematic poverty that today overwhelms us.